The Impact of Effective Coaching on Sales Performance Mediated by the Role of Soft Skills in the Tourism Industry - Mhmood, Mohmmed Raoof; Sani, Mohsen Alizadeh; Safari, Mohammad; Shirkhodaie, Meysam; Azeez, Reyath Thea (Journal of Ecohumanism, 2024)
This research aimed to design a model for the role of effective coaching in achieving sales representatives’ performance through soft skills for Iraqi tourism companies using quantitative and qualitative approaches. A questionnaire was designed to collect data to analyze the relationship between the research variables for (427) paragraphs that were randomly distributed to each tourism salesperson. To prove the model, five hypotheses were formulated where the effect and relationship were proven in all hypotheses using (SPSS, SMART PLS) programs. The results emphasize the importance of implementing strong coaching programs aimed at developing self-awareness, personal responsibility and personal skills among employees. Moreover, the study highlights the need for tourism service providers to comprehensively assess and develop personal skills alongside technical competencies during recruitment and performance management processes. It recommends providing value for the potential benefits of implementing coaching programs to support professional development and enhance the performance of front-line sales personnel. The results of this research can help in developing coaching strategies and coaching programs specifically designed to improve salesperson performance, and ultimately improve customer experience in the tourism services sector.